Synthesis and Antimicrobial Studies of a New Series of Bis-Heterocycles - B. Jayashankara; K.M. Lokanatha Rai (E-Journal of Chemistry)
Series of novel bis-heterocycles bearing isoxazoline and imidazole moieties have been synthesized via 1,3-dipolarcycloaddition reactions. 1HNMR, 13CNMR, IR and elemental analyses characterized the newly synthesized compounds. All the synthesized compounds were evaluated for their antimicrobial activity and were compared with the standard drugs. The compounds demonstrated potent to weak antimicrobial activity.